Kinetic and muscle activity comparisons in race walking and running - Norberg, J.; Varnell, M. (Slovak Journal of Sport Science, 2017)
Race walking is a form of upright locomotion that differs from normal walking and running in that its form is dictated by the International Amateur Athletics Federation (IAAF). Despite the differences compared to running, race walking has not been the subject of equally intensive investigations. This study explores the kinetic and muscle activity differences between race walking and running. A quantitative approach was used to evaluate kinetic and muscle activity variables between race walking and running. A cross-sectional, laboratory design was used on recreationally competitive race walkers to evaluate these variables. Based on the results of the study, significantly greater sagittal plane peak hip flexor, knee extensor moments, and rectus femoris muscle activity contribute to significant difference between race walking and running. These differences showed that running requires more contribution from the lower extremities kinetically, as well as increased overall muscle activation, to execute the motion than race walking. These results likely contributed to the increased velocity of the subjects during running. In spite of these findings, there were some variables that had no significant differences between race walking and running, especially the tibalis anterior activation and the dorsiflexor moment. This suggests that injuries during RW can potentially be similar to those during running. Further research is necessary to see if there is a greater risk of injury in elite-level race walking athletes.